2019
DOI: 10.3390/su11102819
|View full text |Cite
|
Sign up to set email alerts
|

A New Adjustment Strategy to Relieve Inhibition during Anaerobic Codigestion of Food Waste and Cow Manure

Abstract: A new adjustment strategy (controlling temperature, pH, inoculum dose, and liquid supernatant replacement in different digestion stages) was used to relieve volatile fatty acid (VFA) inhibition during anaerobic codigestion of FW and CM. Three digestion stages and groups were designed: initial stage (on days 1–5 the temperature was 45 °C), the second stage (on days 6–10 the temperature was 35 °C and inoculum was supplied), and the third stage (on days 11–50 the temperature was 35 °C and liquid supernatant was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The model results fitted well with the experimental results based on high R 2 (ranged from 0.985 to 0.991) and low RMSE values (ranged from 6.055 to 14.649). Ren et al (2019) also found a very high correlation of methane production using the modified Gompertz equation with a regression coefficient of more than 0.994. Lag time was found to be short (less than 1 day) for all the reactors.…”
Section: Resultsmentioning
confidence: 75%
“…The model results fitted well with the experimental results based on high R 2 (ranged from 0.985 to 0.991) and low RMSE values (ranged from 6.055 to 14.649). Ren et al (2019) also found a very high correlation of methane production using the modified Gompertz equation with a regression coefficient of more than 0.994. Lag time was found to be short (less than 1 day) for all the reactors.…”
Section: Resultsmentioning
confidence: 75%